PENGARUH PENAMBAHAN ABU SERBUK KAYU DAN PASIR BERGRADASI KASAR DALAM MENINGKATKAN KUAT TEKAN PAVING BLOCK - Rosyad, Farlin; Rahman, Robbani; Prawira, Wanda Yudha (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2024)
At present, paving blocks are widely used as building elements for making building construction, especially for yard pavement, parking lots, and environmental roads. Paving blocks are often used because they have good compressive strength properties, can withstand loads within certain limits, longer plan life, and are easy to install. In addition to these advantages, paving blocks are also better than other pavements in terms of economical maintenance, also in terms of the exterior of a building, and also when viewed in terms of environmental sustainability, as a water absorption system. Sawdust is the material (generally powder) that remains from burning wood. Generally, 6-10% of the mass of wood burned produces ash. From the results of research and discussion in the manufacture of paving blocks with wood dust ash additives planned to increase the compressive strength of paving blocks at the age of 28 days, it was found that the compressive strength of normal paving blocks with 0% wood dust ash was 16.08 MPa, while the compressive strength of paving blocks added with wood dust ash with a composition of 5%, 10%, and 15%, produced a compressive strength of 18.05 MPa; 15.24 MPa; 12.20 MPa;. The effect of sawdust ash on the addition of composition materials in the manufacture of paving blocks can increase the compressive strength of the paving block itself. The compressive strength of paving blocks increases after the addition of sawdust ash from the lowest sawdust ash of 0% to 5% ash only, while paving blocks with 10% and 15% sawdust ash experience a significant decrease in compressive strength value from normal sawdust ash. Keywords: Paving Block, Wood Powder Ash